AB0373 Integrating Treatment Goals of Physicians, Patients, and Payers during Treatment with Golimumab in Patients with Rheumatoid Arthritis. (10th June 2014) - Combe, B.; Veale, D.; Burgos-Vargas, R.; Szűcs, G.; Leirisalo-Repo, M.; Yao, R.; Huyck, S.; Lyu, R.; Govoni, M.; Vastesaeger, N.; Weng, H.H.
Abstract : Background: Physicians, patients, and payers may have different ideas about what constitutes successful treatment and how treatment goals should be defined for rheumatoid arthritis (RA). Objectives: To evaluate the overlap between attained treatment goals that are important to physicians, patients, and payers after 6 months of add-on golimumab (GLM) treatment in patients with active RA, and to determine baseline predictors of patients who achieve all 3 treatment goals represented by these stakeholders. Methods: GO-MORE was an open-label, multinational, prospective study in biologic-naïve patients with active RA (28-joint disease activity score using erythrocyte sedimentation rate [DAS28-ESR] ≥3.2) despite disease-modifying antirheumatic drug (DMARD) treatment. Patients received 50-mg subcutaneous (SC) GLM once monthly for 6 months. Efficacy outcomes including DAS28-ESR, patient-acceptable symptom state (PASS), and EuroQol 5-dimension (EQ-5D) were evaluated at month 6. PASS was assessed with 1 yes/no question as to whether the patient would be satisfied to stay in their current disease state. The extent of overlap in achievement of strict remission treatment goals was evaluated (DAS28-ESR remission, normal EQ-5D [≥.8], and met PASS); looser low disease activity (LDA) treatment goals were also evaluated (DAS28-ESR LDA, EQ-5D near normal [≥.7], and met PASS). A multivariate regression analysis identified baseline predictors of patients who achieved the intersection of the 3 criteria. Results: In 3280 efficacy-evaluable patients, mean disease duration was 7.6 years; mean DAS28–ESR was 5.97 (SD=1.095). As previously reported, 23.9% of 3280 efficacy-evaluable patients achieved remission, and 37.4% achieved LDA (based on DAS28-ESR) at month 6. 1 21% of patients achieved normal QoL, and 48% achieved close-to-normal QoL (EQ-5D ≥.7). 66.0% of patients achieved PASS. Overlap in patients who achieved each treatment goal is shown in the figure. 10.7% of patients (350/3280) met all 3 strict criteria, and 25.1% (823/3280) met all 3 looser criteria. Significant baseline predictors of achieving all 3 strict remission criteria were absence of comorbidities; lower DAS28, Health Assessment Questionnaire (HAQ), and swollen joint count scores; and greater anti-cyclic citrullinated peptide levels and EQ-5D Index scores. When PASS was replaced with HAQ ≤.5 (minimal or no functional impairment, achieved by 37.4% of patients) in either the set of strict or looser criteria, the percentage of patients who met all 3 criteria was similar to when PASS was used. Conclusions: In patients with active RA who failed ≥1 DMARD and received add-on GLM for 6 months, overlap in achievement of LDA goals of physicians, patients, and payers was attained in 25.1% of patients. Overlap was smaller when strict remission goals were evaluated. Several measures of lower disease activity at baseline predicted achievement of all 3 strict remission criteria. References: Combe B et al. Ann Rheum Dis. doi:10.1136/annrheumdis-2013-203229. Disclosure of Interest: B. Combe Grant/research support: Pfizer and Roche-Chugai, Consultant for: Merck, Pfizer, Roche-Chugai, and UCB, D. Veale Grant/research support: Abbott, MSD, Pfizer, and Roche, Consultant for: MSD, Pfizer, Roche, and UCB, Speakers bureau: MSD, Pfizer, Roche, and UCB, R. Burgos-Vargas Speakers bureau: BMS, Janssen, Roche, Pfizer, and UCB, G. Szűcs: None declared, M. Leirisalo-Repo Consultant for: MSD, R. Yao Employee of: Merck, S. Huyck Employee of: Merck, R. Lyu Employee of: Merck, M. Govoni Employee of: Merck, N. Vastesaeger Employee of: Merck, H. Weng Employee of: Merck DOI: 10.1136/annrheumdis-2014-eular.1185